2020
DOI: 10.1016/j.sjbs.2020.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Occupational accidents and injuries in construction industry in Jeddah city

Abstract: In Saudi Arabia, the construction industry has been growing remarkably during the past several years. However, the most hazardous worksites in the country may be found in this industry. This study identified the causes of accidents and injuries in the construction industry among 300 workers in Jeddah City, situated on the coast of the Red Sea. Results from the questionnaire showed that the major cause of accidents and injuries is the lack of awareness about occupational safety and lack of experience among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 25 publications
0
27
0
2
Order By: Relevance
“…Due to the high number of accidents in the construction industry of Saudi Arabia [ 6 , 23 , 24 , 25 ], several approaches should be investigated to enhance safety levels at Saudi Arabian construction sites, including safety climate. Currently, there is a lack of research in the area of safety climate in the construction industry of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high number of accidents in the construction industry of Saudi Arabia [ 6 , 23 , 24 , 25 ], several approaches should be investigated to enhance safety levels at Saudi Arabian construction sites, including safety climate. Currently, there is a lack of research in the area of safety climate in the construction industry of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…This study analyzed types of injury and fatal accidents affected by OEQ based on thermal comfort. Most of the earlier works in previous research focused on a specific weather condition, such as those in summer and winter seasons [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. However, the results of this study showed that injury and fatal accidents in the spring and autumn seasons have greater probability than those of the summer and winter seasons.…”
Section: Resultsmentioning
confidence: 99%
“…These weather conditions affect construction workers' thermal comfort. Abukhashabah et al, 2020 [30] The author investigated injuries and causes of incidents in the construction industry in Saudi Arabia, specifically Jeddah. A prevention method was presented to reduce injuries and incidents.…”
Section: Research Related To the Causes Of Construction Disastersmentioning
confidence: 99%
See 2 more Smart Citations